Fabrication of Filament PLA and PLA/HAp - Tunggat, Jerome (Research Progress in Mechanical and Manufacturing Engineering, 2025)
3D printing or additive manufacturing (AM) transforms digital designs into physical objects by layering material sequentially, enabling the creation of complex forms with reduced material waste. Polylactic acid (PLA), a biodegradable and nontoxic material derived from renewable resources, is the most used filament in Fused Deposition Modelling (FDM) due to its ease of use and wide compatibility. Despite its theoretical composability, PLA requires industrial composting facilities for proper degradation. This research aims to fabricate PLA/HAp filaments through the extrusion method and investigate their mechanical, physicochemical, and structural properties. Comprehensive characterization of PLA and PLA/HAp filaments will be conducted to evaluate their potential for advanced additive manufacturing applications. The methodology involves the preparation of high-quality PLA and PLA/HAp filaments through precise extrusion processes, followed by comprehensive analysis of their microstructure, chemical bonding, surface roughness, and mechanical properties. The surface roughness is very crucial, and the highest Roughness Average (Ra) can be found in composition of 70:30 which is 68.974 mm. Modern techniques such as SEM-EDS, FTIR, AFM, and various mechanical tests are utilized to evaluate the quality and potential biomedical applications of the filaments. FTIR, AFM, and SEM-EDS analyses confirm the successful integration of HAp into PLA, revealing increased surface roughness and enhanced mechanical properties with higher HAp content. Tensile, flexural, and bending tests demonstrate improved strength and modulus, indicating the potential of PLA/HAp composites for advanced biomedical applications. This study investigates the mechanical properties, characterization, and physiochemical analysis of PLA/HAp filaments, highlighting their potential in medical applications. FTIR analysis confirmed successful chemical bonding between PLA and HAp, crucial for applications such as tissue engineering and orthopedic implants. Surface roughness and microstructural analyses revealed enhanced properties in PLA/HAp composites, with significant improvements in mechanical strength and biocompatibility.